Conceptualising a Fairness Framework for Assessment Adjusted Practices for Students with Disability: An Empirical Study. Issue 3 (4th May 2021) - Rasooli, Amirhossein; Razmjoee, Maryam; Cumming, Joy; Dickson, Elizabeth; Webster, Amanda
ABSTRACT: Given the increasing diversity of teachers and students in 21 st  century classrooms, fairness is a key consideration in classroom adjusted assessment and instructional practices for students with disability. Despite its significance, little research has attempted to explicitly conceptualise fairness for classroom assessment adjusted practices. The purpose of this study is to leverage the multiple perspectives of secondary school students with disability, their teachers, and parents to build a multi-dimensional framework of fairness for assessment adjusted practices. Open-ended survey data were collected from 60 students with disability, 45 teachers, and 58 parents in four states in Australia and were analyzed using qualitative inductive analysis. The findings present a multidimensional framework for assessment adjusted practices that include interactions across elements of assessment practices, socio-emotional environment, overall conceptions of fairness, and contextual barriers and facilitators. The interactions across these elements influence the learning opportunities and academic outcomes for students with disability.